1997
DOI: 10.1128/jcm.35.6.1353-1360.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of fungal pathogens in blood by using molecular probes

Abstract: A PCR assay was developed for the detection and identification of Candida and Aspergillus species. The design of the oligonucleotide primer pair as well as the species-specific probes used for species identification was derived from a comparison of the sequences of the 18S rRNA genes of various fungal pathogens. The primers targeted a consensus sequence for a variety of fungal pathogens. The assay was tested for sensitivity and specificity with 134 fungal and 85 nonfungal isolates. To assess clinical applicabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
226
2
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(249 citation statements)
references
References 34 publications
13
226
2
5
Order By: Relevance
“…The sensitivity of the assay for invasive candidiasis, including hepatosplenic candidiasis, and aspergillosis was 100% if two specimens were tested, with positive PCR results preceding radiological evidence of infection in the majority of cases. None of the controls were positive and, significantly, only three specimens from three of 36 neutropenic, colonized patients with negative fungal cultures were positive (Einsele et al, 1997).…”
Section: Detection Of Dna Sequencesmentioning
confidence: 90%
See 1 more Smart Citation
“…The sensitivity of the assay for invasive candidiasis, including hepatosplenic candidiasis, and aspergillosis was 100% if two specimens were tested, with positive PCR results preceding radiological evidence of infection in the majority of cases. None of the controls were positive and, significantly, only three specimens from three of 36 neutropenic, colonized patients with negative fungal cultures were positive (Einsele et al, 1997).…”
Section: Detection Of Dna Sequencesmentioning
confidence: 90%
“…Other assays have been developed which utilize serum, plasma or whole blood specimens. Experimental models and clinical studies have shown PCR to be more sensitive than culture for detection of candidaemia (Chryssanthou et al, 1994;van Deventer et al, 1995;Burnie et al, 1997;Einsele et al, 1997;Morace et al, 1999;Wahyuningsih et al, 2000). Einsele used a panfungal PCR assay to retrospectively analyse 601 blood specimens from patients with documented IFI, those with febrile neutropenia with and without colonization, and from controls.…”
Section: Detection Of Dna Sequencesmentioning
confidence: 99%
“…PCR assay. DNA extraction of 10 ml of EDTA-anticoagulated blood was performed using recombinant lyticase (Sigma, Wien, Austria) and the QIAmp Tissue Kit (Qiagen, Wien, Austria), as previously described (Einsele et al, 1997). Genes of the 18S rRNA of various fungal pathogens were amplified by PCR using specific primers.…”
Section: Methodsmentioning
confidence: 99%
“…Polymerase chain reaction may become a diagnostic modality to identify these organisms [139]. Rickerts et al diagnosed disseminated C. bertholletiae infection in a leukaemic patient using a polymerase chain reaction assay targeting 18S ribosomal DNA in blood.…”
Section: Diagnosismentioning
confidence: 99%